(3GdeJZjQGJ GdaSjhdhLjI dMcGe cQI GdSdI GKfGA GdeHGQjGJs - (3GdYRHj QTjOI eMeO MSjfs ((3GdGScfOQjIs (3OGQ GdhaGA dOfjG GdWHGYI h GdfTQs, 2006)
(3jMOO HYV GdeJZjQGJ GdHOfjI h GdhXjajI dMcGe cQI GdSdI CKfGA GdeHGQjGJ,h cjajI JhXjagG CKfGA GdeHGQjGJ, ceG JfGhd HYV GdOQGSGJ GdSGHbI aj gPG GdeLGd h Cge GdfJGFL GdeJhUd EdjgG(B.s